Status Resistensi Nyamuk Aedes aegypti terhadap Malation dan Mutasi Gen Ace-1 di Kota Ambon - Isak Roberth Akollo; Tri Baskoro Satoto; Sitti Rahmah Umniyati (Jurnal Vektor Penyakit, 2020)
Abstract Aedes aegypti is the main vector of Dengue Hemorrhagic Fever (DHF). The continuous use of insecticides can cause resistant Ae. aegypti. One indicator of mosquito resistance to organophosphate is acetylcholinesterase insensitivity, which is encoded by the ace-1 gene. This study aims to analyze the status of resistance and detect ace-1 gene mutations in Ae. aegypti in Ambon city. This research is a descriptive and analytic study with a cross-sectional research design. Resistance status was tested by the CDC bottle bioassay and the detection of ace-1 gene mutations was established using PCR and sequencing. The nucleotide sequence was edited with Mega 7 software. The results of resistance tests using the CDC bottle bioassay method showed Ae. aegypti from the Waihaong and Rijali Community Health Centers had a mortality of 92% and 95.83% (tolerant), while the Latuhalat, Amahusu, Air Salobar, Benteng, Urimessing, Christina Martha Thiahahu, Karpan, Belso, Air Besar, Kilang, Halong, Lateri, Passo, and Nania had mortality between 98-100% (vulnerable). Sequencing and alignment results showed that there were no ace-1 gene mutations in Ae. aegypti originating from Waihaong and Rijali Community Health Centers. Ae. aegypti resistance status in 2 Community Health Centers is tolerant and 14 other Community Health Centers are vulnerable. There are no ace-1 gene mutations in Ae. aegypti at the Waihaong and Rijali Community Health Centers in Ambon City. Abstrak Nyamuk Aedes aegypti adalah vektor utama penyakit demam berdarah dengue (DBD). Penggunaan insektisida terus menerus dapat menyebabkan nyamuk Ae. aegypti resisten. Salah satu indikator resistensi nyamuk terhadap insektisida organofosfat adalah insensitivitas acetylcholinesterase, yang dikode oleh gen ace-1. Penelitian ini bertujuan menganalisis status resistensi dan mendeteksi mutasi gen ace-1 pada nyamuk Ae. aegypti di kota Ambon. Penelitian ini merupakan penelitian deskriptif dan analitik dengan rancangan penelitian cross sectional. Status resistensi diuji dengan metode CDC bottle bioassay dan deteksi mutasi gen ace-1 ditegakkan menggunakan PCR dan sekuensing. Urutan nukleotida diedit dengan software Mega 7. Hasil uji resistensi dengan metode CDC bottle bioassay menunjukan nyamuk Ae. aegypti dari Puskesmas Waihaong dan Rijali memiliki mortalitas 92% dan 95,83% (toleran), sedangkan Puskesmas Latuhalat, Amahusu, Air Salobar, Benteng, Urimessing, Chrsitina Martha Thiahahu, Karpan, Belso, Air Besar, Kilang, Halong, Lateri, Passo, dan Nania memiliki mortalitas antara 98-100% (rentan). Hasil sekuensing dan alignment menunjukan tidak terdapat mutasi gen ace-1 pada nyamuk Ae. aegypti yang berasal dari Puskesmas Waihaong dan Rijali. Status resistensi nyamuk Ae. aegypti di 2 Puskesmas Kota Ambon tergolong toleran dan 14 Puskesmas lainnuya tergolong rentan. Tidak terdapat mutasi gen ace-1 pada nyamuk Ae. aegypti di Puskesmas Waihaong dan Rijali Kota Ambon.